2017
DOI: 10.3390/children5010005
|View full text |Cite
|
Sign up to set email alerts
|

Role of RDW in Prediction of Burn after Caustic Substance Ingestion

Abstract: A quantifiable, quick, inexpensive and reproducible predictor is needed to decide if caustic substance ingestion results in burn regardless of the symptoms. A multicenter cohort study was conducted to investigate the predictive value of red cell distribution width (RDW) in detecting the esophageal burns. The data of 174 patients were retrospectively analyzed. Eleven patients were excluded due to inability to define the substance ingested. Complete blood count (CBC) was taken at admission, and an esophagogastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The RDW has 84.2% sensitivity, 59.2% specificity, 38.6% PPV, and 92.5% NPV for severe esophageal injuries. 17 Pediatric Early Warning System (PEWS) and Drooling Reluctance Oropharynx Other Leukocytosis (DROOL) score was studied in Egypt and Saudi Arabia as prognostic predictor in pediatric esophageal strictures. Median PEWS in good outcome group was 3 (1-8), while median PEWS in poorer outcome was 13 (9.3-17) (p<0.001).…”
Section: Predictors Of Severity Of Caustic Injuries and Prognosismentioning
confidence: 99%
“…The RDW has 84.2% sensitivity, 59.2% specificity, 38.6% PPV, and 92.5% NPV for severe esophageal injuries. 17 Pediatric Early Warning System (PEWS) and Drooling Reluctance Oropharynx Other Leukocytosis (DROOL) score was studied in Egypt and Saudi Arabia as prognostic predictor in pediatric esophageal strictures. Median PEWS in good outcome group was 3 (1-8), while median PEWS in poorer outcome was 13 (9.3-17) (p<0.001).…”
Section: Predictors Of Severity Of Caustic Injuries and Prognosismentioning
confidence: 99%
“…Prediction of the presence and severity of GIT injury post caustic ingestion is a challenging problem; several studies have shown that clinical manifestations are not always good predictors for the degree of injury and possible outcomes occurrence (Tosca et al, 2021). Also there is a debate about performing esophagogastroduodenoscopy or computerized tomography for early caustic ingestion evaluation especially in children, owing to the associated high risks, unavailability and the need for highly qualified health professionals (Aydin et al, 2017;Kamat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%